Transcriptomic analysis and 3D bioengineering of astrocytes indicate ROCK inhibition produces cytotrophic astrogliosis - O'Shea, Ross D.; Lau, Chew L.; Zulaziz, Natasha; Maclean, Francesca L.; Nisbet, David R.; Horne, Malcolm K.; Beart, Philip M. (Frontiers in Neuroscience, 2015)
Astrocytes provide trophic, structural and metabolic support to neurons, and are considered genuine targets in regenerative neurobiology, as their phenotype arbitrates brain integrity during injury. Inhibitors of Rho kinase (ROCK) cause stellation of cultured 2D astrocytes, increased L-glutamate transport, augmented G-actin, and elevated expression of BDNF and anti-oxidant genes. Here we further explored the signposts of a cytotrophic, “healthy” phenotype by data-mining of our astrocytic transcriptome in the presence of Fasudil. Gene expression profiles of motor and autophagic cellular cascades and inflammatory/angiogenic responses were all inhibited, favoring adoption of an anti-migratory phenotype. Like ROCK inhibition, tissue engineered bioscaffolds can influence the extracellular matrix. We built upon our evidence that astrocytes maintained on 3D poly-ε-caprolactone (PCL) electrospun scaffolds adopt a cytotrophic phenotype similar to that produced by Fasudil. Using these procedures, employing mature 3D cultured astrocytes, Fasudil (100 μM) or Y27632 (30 μM) added for the last 72 h of culture altered arborization, which featured numerous additional minor processes as shown by GFAP and AHNAK immunolabelling. Both ROCK inhibitors decreased F-actin, but increased G-actin labeling, indicative of disassembly of actin stress fibers. ROCK inhibitors provide additional beneficial effects for bioengineered 3D astrocytes, including enlargement of the overall arbor. Potentially, the combined strategy of bio-compatible scaffolds with ROCK inhibition offers unique advantages for the management of glial scarring. Overall these data emphasize that manipulation of the astrocyte phenotype to achieve a “healthy biology” offers new hope for the management of inflammation in neuropathologies.